Impact of Islamic leadership, motivation, and work-life balance on performance: A gender analysis - Suradi, Romi; Mamduh, Muhammad Faizul; Ali, Mohammad Mahbubi; Setianingsih, Hesti Eka; Cholil, Muhammad (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study aims to analyze the effect of Islamic leadership on employee performance by integrating Islamic work motivation, work environment, and work-life balance (WLB) as mediating and contextual factors, while also examining gender differences through Multi-Group Analysis (MGA).Methodology – This study employs a quantitative approach with survey data collected from 80 employees working in Islamic banking and financial institutions and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings – The findings indicate that Islamic work motivation significantly enhances employee performance, both directly and indirectly, through WLB. In contrast, Islamic leadership and the work environment do not have a direct significant effect on employee performance, highlighting the need for more consistent application of Islamic leadership values. The MGA results reveal no significant gender difference in the influence of Islamic leadership on employee performance but show that women face greater challenges in achieving WLB, reflecting their dual roles in professional and personal spheres.Implications – The findings imply that organizations should strengthen the implementation of Islamic leadership values consistently, promote Islamic work motivation, and design inclusive policies that address gender-specific challenges in achieving work-life balance. Originality – This study offers originality by explicitly integrating gender dynamics into an Islamic leadership framework. Unlike previous studies that focus mainly on the general aspects of Islamic leadership, this research highlights how gender differences, particularly women’s dual roles, shape the relationship between Islamic leadership, work-life balance, and employee performance.